Mikulicz’s Disease With Immune Thrombocytopenia: A New Immunoglobulin G4-Mediated Disorder and Literature Review - Shu LI,; Cong DENG,; Jinwei CHEN,; Fen LI, (Archives of Rheumatology, 2019)
Mikulicz’s disease (MD), an immunoglobulin G4 (IgG4)-related disease, is a fibrosis-associated inflammatory disease characterized by painless bilat- eral swelling of lacrimal and salivary glands. Although thrombocytopenia is associated with many rheumatologic disorders, it is rare in IgG4-related MD. This novel study aims to report a rare case of IgG4-related MD complicated with severe autoimmune thrombocytopenia without any hemato- logical malignancies and review all cases of IgG4-related disease associated with thrombocytopenia in the literature.